The Internationalization of Currencies : An Appraisal of the Japanese Yen - Ozeki, Yusuru; Tavlas, George (Washington, D.C. : International Monetary Fund, 1992)
A tripolar international monetary system-centered on the U.S. dollar, the deutsche mark, and the yen - appears to be emerging. This paper not only assesses the role of the yen as an international currency but also presents a unified theory of international currency use and distinguishes between the roles of a nation as a world banker and as an international financial intermediary.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet